SEG Technical Program Expanded Abstracts 2015 2015
DOI: 10.1190/segam2015-5882173.1
|View full text |Cite
|
Sign up to set email alerts
|

Effective-Medium Anisotropic models of Fractured Rocks of TI Symmetry: Analysis of Constraints and Limitations in Linear Slip model

Abstract: The simplest effective-medium model of fractured rocks known as the Linear Slip (LS) model of Schoenberg (1980) represents a single fracture set in an isotropic background rock. In the LS model, the stiffness C 13 is not independent as in the overall transversely isotropic (TI) model, but it is related to other stiffnesses by the equation, C 11 C 33-C 2 13 = 2C 66 (C33+C13). We have studied a physical sense of this constraint on the C 13 and found out that in terms of the TI elastic compliance tensor S it lead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0
7

Year Published

2016
2016
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 27 publications
1
2
0
7
Order By: Relevance
“…The second observation is more concerning given that the LS model is used pervasively in the seismological community. Chichinina et al (2015) analyse the limitations of Schoenberg & Sayers (1995) LS model and find that their model is not generally adequate for real rocks. Chichinina et al (2015) note that the LS model is only valid for two conditions: (1) when Z N = 0 (i.e., case of fluid-filled fractures) or (2) when the scalar crack Z N /Z T = 1 is assumed (i.e., Bakulin et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The second observation is more concerning given that the LS model is used pervasively in the seismological community. Chichinina et al (2015) analyse the limitations of Schoenberg & Sayers (1995) LS model and find that their model is not generally adequate for real rocks. Chichinina et al (2015) note that the LS model is only valid for two conditions: (1) when Z N = 0 (i.e., case of fluid-filled fractures) or (2) when the scalar crack Z N /Z T = 1 is assumed (i.e., Bakulin et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Chichinina et al (2015) analyse the limitations of Schoenberg & Sayers (1995) LS model and find that their model is not generally adequate for real rocks. Chichinina et al (2015) note that the LS model is only valid for two conditions: (1) when Z N = 0 (i.e., case of fluid-filled fractures) or (2) when the scalar crack Z N /Z T = 1 is assumed (i.e., Bakulin et al, 2000). Hildyard (2001) observed that the LS model was only accurate for high-stiffness fractures and became increasingly inaccurate as the stiffness decreased, which is consistent with the first condition Z N = 0.…”
Section: Discussionmentioning
confidence: 99%
“…И не только оно, а и исходное условие-огра-ничение на s 13 в модели LS VTI, s 13 = s 12 , из которого оно получено при переходе от матрицы VTI S к матри-це VTI C : VTI VTI 1 ( ) − = C S . Об этом факте мы сообщи-ли в докладах на конференциях EAGE и SEG [Чичи-нина и др., 2015а; Chichinina et al, 2015].…”
Section: анализ условия-ограничения на константу C 13 в модели Ls Tiunclassified
“…По-казаны ограниченные возможности использования данной модели, которые связаны с произволом в вы-боре пятой константы с 13 , в результате которого полу-чаемая матрица жесткости теряет физический смысл и не отвечает принципу симметрии Кюри. Выполнен-ное нами исследование модели разрыва смещений представлено в сжатом виде в расширенных тезисах докладов на конференциях SEG и EAGE [Чичинина и др., 2015а; Chichinina et al, 2015].…”
Section: Introductionunclassified
“…Причинами ее популярности являются умень шенное количество независимых элементов мат-рицы жесткости, описывающей среду с параллельными трещинами (четыре вместо пяти), и введение характе-ристик трещиноватости непосредственно в элементы матрицы жесткости. Однако как показал выполненный нами анализ этой модели [Чичинина и др., 2015, 2016Chichinina et al, 2015], она не имеет физического смыс ла и не соответствует принципу симметрии Кюри. Применять ее можно только в случае распространения упругих волн по нормали к плоскостям трещин, т. е. вдоль оси симметрии среды, и в плоскости трещин, плоскости изотропии.…”
Section: Introductionunclassified